The Ethics of Influence: A Review of Nudging Applications in Corporate Ethics and Their Role in Combating Organizational Misconduct - Mohammad Chaidir; Novrizal Novrizal (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores the role of behavioral nudging as a tool for enhancing corporate ethics and curbing organizational misconduct. Drawing on empirical and theoretical studies from behavioral ethics, organizational psychology, and compliance management, the review examines how subtle interventions—such as reminders, social norm cues, and visual prompts—can influence ethical decision-making in the workplace. The findings suggest that nudges are effective in reducing ethical fading, improving compliance, and reinforcing ethical culture when aligned with organizational values and context. However, concerns regarding manipulation, cultural adaptability, and long-term efficacy remain. This review highlights the importance of integrating nudging within a broader ethical infrastructure and calls for future research on scalable, transparent, and culturally sensitive applications of ethical influence in diverse organizational settings